1998
DOI: 10.1007/978-94-011-4786-6_20
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis-resistant NS/0 E1B-19K myelomas exhibit increased viability and chimeric antibody productivity under cell cycle modulating conditions

Abstract: Lymphoid cells expressing sufficient levels of Bcl-2 or E1B-19K are known to resist to induction of apoptosis in glutamine-free or nutrient-limited batch cultures. However, despite the increased viability and prolonged stationary phase achieved in batch culture, product yields are not necessarily improved. Here we have found that expression of E1B-19K in NS/0 myeloma cells cultivated in the presence of certain cell cycle modulators could result in a significant increase in MAb productivity as compared to untra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 63 publications
(37 reference statements)
0
14
0
Order By: Relevance
“…This has been observed for cells cultivated in batch (Ramirez and Mutharasan, 1990), fed-batch (de Tremblay et al, 1993;Robinson et al, 1994), chemostat (Boraston et al, 1984), and perfusion modes (Al-Rubeai et al, 1992;Banik and Heath, 1995;Batt et al, 1990;de la Broise et al, 1991;Johnson et al, 1996;Hansen et al, 1993;Park and Ryu, 1994;Tokashiki and Takamatsu, 1993;Trampler et al, 1994), as well as in cells treated with cell-cycle blocking agents (Al-Rubeai and Emery, 1990;Jayme, 1991;Mercille and Massie, 1998;Oh et al, 1995;Øyaas et al, 1994a,b;Reddy and Miller, 1994;Suzuki and Ollis, 1990;Takahachi et al, 1994). Indeed, specific antibody production has been shown to be cell cycle dependent and optimum in the G 1 and/or G 2 /M phase (Cazzador and Mariani, 1993;Kromenaker and Srienc, 1991;Linardos et al, 1992;Richieri et al, 1991;Suzuki and Ollis, 1989).…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…This has been observed for cells cultivated in batch (Ramirez and Mutharasan, 1990), fed-batch (de Tremblay et al, 1993;Robinson et al, 1994), chemostat (Boraston et al, 1984), and perfusion modes (Al-Rubeai et al, 1992;Banik and Heath, 1995;Batt et al, 1990;de la Broise et al, 1991;Johnson et al, 1996;Hansen et al, 1993;Park and Ryu, 1994;Tokashiki and Takamatsu, 1993;Trampler et al, 1994), as well as in cells treated with cell-cycle blocking agents (Al-Rubeai and Emery, 1990;Jayme, 1991;Mercille and Massie, 1998;Oh et al, 1995;Øyaas et al, 1994a,b;Reddy and Miller, 1994;Suzuki and Ollis, 1990;Takahachi et al, 1994). Indeed, specific antibody production has been shown to be cell cycle dependent and optimum in the G 1 and/or G 2 /M phase (Cazzador and Mariani, 1993;Kromenaker and Srienc, 1991;Linardos et al, 1992;Richieri et al, 1991;Suzuki and Ollis, 1989).…”
Section: Introductionmentioning
confidence: 84%
“…In perfusion, this clone exhibited a steady-state MAb concentration of 247 ± 15 mg/L throughout the plateau phase, representing more than 2.8-fold what was found in batch culture. In the case of E1B-19K cells, a maximal MAb concentration of 33 mg/L could be found at the end of the control batch culture performed on cells taken out of the perfusion bioreactor (see also Mercille et al, 1999;Mercille and Massie, 1998). In perfusion, the E1B-19K cell line exhibited a steady-state MAb concentration of 231 ± 12 mg/L throughout the plateau phase.…”
Section: Effect Of E1b-19k On Mab Concentration and Specific Chb43 Mamentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that cells exposed to slow growth conditions under adequate nutrient supply will exhibit increased MAb secretion rates (Takahashi et al, 1994). However, arresting cells using cytostatic agents results in a rapid induction of apoptosis in non-protected cells (Singh et al, 1994;Mercille and Massie, 1998). Anti-apoptotic genes such as Bcl-2 or E1B-19K can contribute to a significant increase in cell survival in the presence of these cell-cycle blocking agents (Singh et al, 1996).…”
Section: Transfection Screening and Characterization Of Apoptosis-rmentioning
confidence: 99%
“…Anti-apoptotic genes such as Bcl-2 or E1B-19K can contribute to a significant increase in cell survival in the presence of these cell-cycle blocking agents (Singh et al, 1996). We have recently observed that under slow growth conditions achieved following supplementation with OptiMabs (Gibco) (Mercille and Massie, 1998) or in perfusion culture mode (Mercille and Massie, 1999), E1B-19K-expressing cells exhibited a greater increase in productivity as compared to nonprotected cells.…”
Section: Transfection Screening and Characterization Of Apoptosis-rmentioning
confidence: 99%